2011
DOI: 10.1177/0956247811418739
|View full text |Cite
|
Sign up to set email alerts
|

Implementing urban participatory climate change adaptation appraisals: a methodological guideline

Abstract: This paper provides conceptual and methodological guidelines for researchers seeking to undertake an urban participatory climate change adaptation appraisal (PCCAA), illustrated with examples from appraisals in Mombasa (Kenya) and Estelí (Nicaragua). It highlights the importance of hearing local people's voices regarding incrementally worsening and often unrecorded severe weather. The conceptual framework distinguishes between the analysis of asset vulnerability and the identification of asset-based operationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 15 publications
0
36
0
2
Order By: Relevance
“…The design of the focus groups was adapted from a participatory methodology developed by McIlwaine (1999, 2004). The focus groups consisted of a number of ranking, listing and mapping exercises which have been shown to be useful in collecting data on urban livelihoods (see Moser and Stein, 2011). Building on previous experiences with this methodology, the compositions of the focus groups were designed to promote different dynamics ( e.g.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…The design of the focus groups was adapted from a participatory methodology developed by McIlwaine (1999, 2004). The focus groups consisted of a number of ranking, listing and mapping exercises which have been shown to be useful in collecting data on urban livelihoods (see Moser and Stein, 2011). Building on previous experiences with this methodology, the compositions of the focus groups were designed to promote different dynamics ( e.g.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…More specifically, impacts of flood events and factors that intensify the impacts on livelihoods assets of the urban poor are examined. This methodology further aids the understanding of community perceptions and responses to urban hazards as it will assist in the development of specific strategies for urban resilience in the study area as had been demonstrated in the work of Moser and Stein (2011).…”
Section: Methodology and Analytical Frameworkmentioning
confidence: 97%
“…Recently, Caroline Moser worked with other researchers and authors to address particular problems associated with climate change using an asset-based approach (see Moser & Satterthwaite 2010;Moser & Stein 2011;Stein & Moser 2014). These researchers focus on three components -asset vulnerability, asset adaptation strategies and asset planning for climate change adaptation -and they discuss context-specific hazards and possible adaptation strategies identified by communities living in informal settlements in different locations.…”
Section: Introductionmentioning
confidence: 97%